The influence of age and sex on the vocal repertoire of the Antillean manatee (Trichechus manatus manatus) and their responses to call playback. Issue 3 (26th December 2017) - Umeed, Rebecca; Niemeyer Attademo, Fernanda Löffler; Bezerra, Bruna
Abstract: Limited information is available regarding the acoustic communication of Antillean manatees, however, studies have shown that other manatee taxa produce vocalizations as a method of individual recognition and communication. Here, the acoustic signals of 15 Antillean manatees in captivity were recorded, aiming to (1) describe their acoustic repertoire, (2) investigate the influence of sex and age on vocalization, and (3) examine manatee responses to call playback. Six acoustic signals ranging in mean fundamental frequencies from 0.64 kHz to 5.23 kHz were identified: squeaks and screeches were common to adult males, adult females, and juveniles; trills were common to adult males and females; whines were specific to males; creaks were specific to females; and rubbing was specific to juveniles. The structure of squeak vocalizations was significantly different between age and sex classes and screech structure was significantly different between age classes. Squeaks and screeches produced by juveniles had higher frequencies of maximum energy when compared to those produced by adult males and females. A significant increase in the vocalization rate following vocalization playbacks was found for all three age/sex groups. Our results introduce the potential of using acoustic signals in identifying and noninvasively monitoring manatees in the wild in Brazil.